A Single Electrode Organic Neuromorphic Device for Dopamine Sensing in Vivo - Federico Rondelli; Michele Di Lauro; Gioacchino Calandra Sebastianella; Anna De Salvo; Matteo Genitoni; Mauro Murgia; Pierpaolo Greco; Carolina Giulia Ferroni; Riccardo Viaro; Luciano Fadiga; Fabio Biscarini (Advanced Electronic Materials)
Abstract Organic Electronic platforms for biosensing are being demonstrated at a fast pace, especially in healthcare applications where the use of organic (semi‐)conductive materials leads to devices that efficiently interface living matter. Nevertheless, interesting properties of organic (semi‐)conductors are usually neglected in the development of (bio‐)sensors. Among these, the non‐linear response when operated under dynamic biasing conditions (i.e., with pulsed driving voltages), thus mimicking synaptic plasticity phenomena, offers promising and largely unexplored possibilities for bio‐sensing. The artificial synaptic response's figures of merit reflect the composition of the surrounding environment and, ultimately, the ion concentration and dynamics at the organic (semi‐)conductor/electrolyte interface. Therefore, new sensing strategies that rely on the effect of target analytes on the short‐term plasticity response of Organic Neuromorphic Devices are being demonstrated. This work presents the development of a label‐free Single Electrode Neuromorphic Device (SEND) specifically designed for in vivo real‐time mapping of dopamine concentration. The device response is investigated as a function of the driving frequency, resulting in the determination of the optimal operational configuration for minimally invasive neuromorphic devices. It exhibits stable multi‐parametric response in complex fluids, in brain's mechanical models and in vivo, enabling monitoring of local variations of dopamine concentration in the rat brain.